The Development of Klidang Lor Port Batang, 1975-2014 - Abdirozaq, Mifta; Rochwulaningsih, Yety; Alamsyah, Alamsyah (Indonesian Historical Studies, 2023)
Klidang Lor Port was administratively established in 1975 after being separated from Pekalongan Port. Using historical methods, this article aims to analyze the development of facilities and activities at Batang Port from the New Order era to the Reformation period. In the period 1975-1988, fish production increased due to the development of motorboats which were previously traditional vessels. In 1988-1998, the port authority built a harbor pier and lighthouse to make it easier for ships to dock. Port facilities continued to be built until the 1998-2007 period. This article analyzes the productivity of fishermen around Klidang Lor Harbor along with the addition of port facilities. The research results show that one of the facilities at the port that has a significant impact is the Public Fuel Filling Station (SPBU). Apart from that, the change in status from Fishing Port to Klidang Lor Coastal Fishing Port (KPBU) has also increased fishermen's productivity because port facilities continue to be developed.